EKSISTENSI ANAK PEREMPUAN DALAM HUKUM KEWARISAN SYIAH - Rama, Faby Toriqir (Program Studi Hukum Keluarga Islam Fakultas Syariah dan Hukum, 2019)
This is a bibliographical research that discusses the justice of girls in Shi?ah inheritance system. The issue which is the subject of discussion is the position of female heirs, especially girls, who in Sunni inheritance system is not treated equally with other heirs, whether they are equal or not. Because in the Sunni inheritance system, male superiority is highly exalted. Between sons and daughters, even though they are equal in the eyes of the heir, still have an unbalanced power in veiling other heirs. Whereas in Shi?ah inheritance system, girls are positioned as equals to boys. They have the same hijab power. In addition, Presidential Instruction No. 1 of 1991 concerning Compilation of Islamic Law (KHI) also applies the principle of equality between girls and boys in terms of veiling other heirs. Nevertheless, KHI did not adopt the class system directly. However, it is explicitly stated in article 181 and article 182 that the existence of a daughter causes sibling,  sibling  with the same mothe or sibling with the same father does not receive part of the inheritance.